Estudio económico de las necesidades básicas del recinto los palmares del cantón El Empalme, con el propósito de elaborar un plan de desarrollo social para el periodo 2014-2018 - Aguila Núñez, Nora Isabel (2013)
The venue's main economic activity is agriculture Palmares, among which include the production of corn, coffee, cocoa, passion fruit, cattle and pig raising, among others. The Campus Palmares has thirty-five years of creation and there is little that so far have made local and provincial authorities to address their most important needs, hence it is obvious neglect and backwardness which has undergone. The research developed, envisioned that the 42.86% of respondents have between 1 and 2 children per family. While the 31.32% reported 3 to 4 children. The 76.92% of the population aged 0-12 years are enrolled in basic education. The 44.44% of adolescents aged 12-18 and 57.45% between 25 and 65 said they have the same level of education. The 40.66% of the population have average monthly income between USD 201 and USD 300. For the 25.82% income range between USD 0 and USD 200. The 18.68% with revenues ranging from USD 300 to USD 500. To a lesser extent, the 5.49% obtained revenues exceeding USD 500. According 53.85% of the respondents, the walls of their houses are made of cement, while 29.67% said they were wooden. The 10.99% of the population has bamboo walls. The 86.81% vital fluid is supplied by a well or shed, while 75.82% do not have phone service conventionally provided through public networks. The 96.15% eliminates their excreta through septic tank or cesspool. The 60.99% of respondents in their homes live in quarter 1 to 2 people, followed by 15.38% who said there are on average between 2 and 3 people. According to 71.98% of the respondents in their homes all his children attend educated in the various establishments. The 13.19% said that one of its members do not attend school, while 10.99% said that 2 children not attending an educational institution. Respondents expressed that households composed xvi of 1 member 66.67% have passed between 1st and 2nd year, while 84% have passed between 8th and 10th grade, while 50% have between 1 and 4 the year of approved college.